2022
DOI: 10.1039/d2sc00763k
|View full text |Cite
|
Sign up to set email alerts
|

Mining anion–aromatic interactions in the Protein Data Bank

Abstract: Mutual positioning and non-covalent interactions in anion-aromatic motifs are crucial for functional performance of biological systems. In this context, regular, comprehensive Protein Data Bank (PDB) screening that involves various scientific...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 103 publications
(143 reference statements)
0
11
0
Order By: Relevance
“…It is interesting that the structure displays bifurcated N–H···O interactions in which the nitrogen atom of HL ’s amino group functions as a hydrogen bond donor with two separate oxygen acceptors while O5 from the nitrate ion acts as a bifurcated acceptor for two distinct donors from HL (N3 and C18) (see Figure ). Furthermore, hydrogen bonds and π···π (with a centroid···centroid separation of 3.787 Å) and anion···π interactions , (with a centroid···O separation of 3.796 Å) between the nitrate ion and the amino group of HL generate the third dimension along the b -axis (see Figure ). The presence of the nitrate anion is particularly significant in the expansion and stability of this supramolecular network, as shown by the structure of this complex.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting that the structure displays bifurcated N–H···O interactions in which the nitrogen atom of HL ’s amino group functions as a hydrogen bond donor with two separate oxygen acceptors while O5 from the nitrate ion acts as a bifurcated acceptor for two distinct donors from HL (N3 and C18) (see Figure ). Furthermore, hydrogen bonds and π···π (with a centroid···centroid separation of 3.787 Å) and anion···π interactions , (with a centroid···O separation of 3.796 Å) between the nitrate ion and the amino group of HL generate the third dimension along the b -axis (see Figure ). The presence of the nitrate anion is particularly significant in the expansion and stability of this supramolecular network, as shown by the structure of this complex.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the anion interacting with the π region of the aromatic rings, its interaction with the edge of the ring is also frequent in proteins and is referred to as the anion–aromatic or anion–quadrupole interaction (Figure D). The distance of ≤4.5 Å between the ring center and anion implies a favorable interaction that is driven by electrostatics. , The calculated strength of this edgewise interaction can be up to −8.0 kcal mol –1 . , A PDB survey indicates that aromatic residues prefer an anion–quadrupole more than an anion−π interaction, possibly because of the unfavorable interaction between these electron-rich moieties . Of all of the aromatic residues interacting with anions, 62.9% of His, 55.3% of Tyr, 46.4% of Trp, and 27% of Phe residues form the anion–quadrupole interaction . On the contrary, only up to ∼8% of these residues interact with anions via the π region to form an anion−π interaction .…”
Section: Anion···π and Anion–aromatic Interactionsmentioning
confidence: 99%
“…with the anion localized over the ring, or ‘peripheral’, i.e. with the anion close to the ring plane or above the ring substituents ( 55 ). This study confirmed the abundance of anion…aromatic interactions in basically all investigated systems and showed that nucleobases and ligands exhibit a considerable preference for ‘canonical’ anion…π contacts.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of RNA, when the current view in chemistry was that forces between anions and the seemingly electron-rich π-system of an aromatic ring could be repulsive ( 56 ), it was debated whether such an interaction would be a stabilizing or a merely tolerated short contact ( 36 ). Nowadays, the anion…π stacking contact between phosphate and uracil is known to occur in 3- and 4-nt U-turns ( 29 , 36 , 57 ), and the contact between phosphate and guanine is described as a conserved and key feature of GNRA tetraloops (frequently occurring structural motifs, where N stands for any nucleobase and R stands for A or G) ( 29 , 55 ). In addition, by quantum mechanics (QM) calculations, this specific interaction between a phosphate and a guanine two residues upstream in the context of GNRA motifs has been estimated to be stabilizing by 3–4 kcal•mol −1 ( 58 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation